Developing water indices for distributing increased Nile water yield among the Nile Basin countries - Ali, Hesham Mostafa, author; Mahmoud, Mohamed Rami, author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 1998)
The River Nile is one of the longest rivers in the world. It is shared by ten countries, all in varying states of development. Numerous studies indicate Nile water resources are not fully utilized. In fact, the Nile Basin's riparian countries utilize less than 50% of the river's total water resources. Cooperation amongst these countries has been recently encouraged to decrease river water losses and increase the water yield. In this study, expected water yield increase (losses saved) is divided amongst the riparian countries based upon each country's ''water index". These indices are developed using several parameters that characterize/individualize each country, including its present available water resources and average water per capita as well as its population, average income, future water demand and the dependence of the country's income on agriculture and other resources. It was found that the most critical and difficult aspects of developing such indices is interlinking economic, social, institutional and environmental factors. All considered, the water index has a substantial and potentially equitable effect when estimating each country's share of the increased water yield.
USCID conference on shared rivers
Distributing increased Nile water yield
Not digitized by CSUL Digital Services.
Presented at River basin management to meet competing needs: proceedings from the USCID conference on shared rivers held on October 21-31, 1998 in Park City, Utah.